Oposisi Dongeng Dalam Channel Youtube Indonesian fairy Tales (Kajian Intertekstual Julia Kristeva) - Khairunnisa Khairunnisa; Nensilianti Nensilianti; Suarni Syam Saguni (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. Fairy tale opposition in the Indonesian fairy tales youtube channel: Julia Kristeva's intertextual study. This study aims to describe the opposition that occurs in four fairy tales contained in the Indonesian Fairy Tales Youtube Channel using Julia Kristeva's intertextual study. This research is descriptive qualitative. The data of this study are in the form of quotations from fairy tales that show the opposition that occurs between individuals and groups. The results of this study are in the form of something opposite that cannot be exchanged and absolute between two competitive groups, never get along, never complement each other and can never be reconciled. Keywords: intertextual, opposition